2019
DOI: 10.4254/wjh.v11.i6.542
|View full text |Cite
|
Sign up to set email alerts
|

Validation of modified albumin-bilirubin-TNM score as a prognostic model to evaluate patients with hepatocellular carcinoma

Abstract: BACKGROUND An ideal staging system for hepatocellular carcinoma (HCC) should rely on the hepatic reserve function and tumor burden. With the improvement in diagnostic and treatment strategies for HCC, in addition to recent treatment of viral hepatitis, finding a suitable assessment tool for hepatic reserve has become mandatory. AIM To validate a recently proposed modified albumin-bilirubin-TNM (mALBI-T) grade as a prognostic model for patients with HCC in Egypt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In our study, we found that PALBI grade was superior to ALBI grade and CTP class in predicting OS of patients with large HCCs after TACE-MWA. These findings are consistent with those of previous studies [30,38]. The CTP classification was originally developed to assess hepatic function in patients with hepatic cirrhosis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, we found that PALBI grade was superior to ALBI grade and CTP class in predicting OS of patients with large HCCs after TACE-MWA. These findings are consistent with those of previous studies [30,38]. The CTP classification was originally developed to assess hepatic function in patients with hepatic cirrhosis.…”
Section: Discussionsupporting
confidence: 90%
“…The PALBI score was calculated using the following equation: PALBI score ¼ 2.02 Â log 10 bilirubin À 0.37 Â (log 10 bilirubin) 2 À 0.04 Â albumin À 3.48 Â log 10 platelets þ 1.01 Â (log 10 platelets) 2 . The PALBI grade was defined as follows: grade 1 (PALBI score À2.53); grade 2 (-2.53 < PALBI score -2.09); and grade 3 (PALBI score >-2.09) [30,33].…”
Section: Definition Of Albi Grade and Palbi Gradementioning
confidence: 99%
See 2 more Smart Citations
“…ALBI, [7] PALBI [8] and ALBI-PLT [9] are models for assessment of the liver condition without subjective bias. They are based on routine simple investigations.…”
Section: Discussionmentioning
confidence: 99%